Upaya Perlindungan Hak Kekayaan Intelektual (HKI) terhadap Usaha Mikro Kecil dan Menengah (UMKM) - Tarigan, Emi Yani Teta Br; Adelia, Adelia; Dalimunthe, Nikmah (Maliyah : Jurnal Hukum Bisnis Islam, 2023)
UMKM are one of the factors driving the country's economy. In this case, there is still a lack of government attention in protecting and prospering the fate of UMKM entrepreneurs. Protection efforts are needed to maintain the existence and originality of each product that has special value and characteristics produced by its creator through thinking called creativity. The problems raised in this journal discuss how efforts or forms of HKI protection in Indonesia for UMKM, especially in the creative industry, how efforts are made to apply HKI to UMKM, and what are the procedures for registering a product or service into HKI as a form of protecting the results of one's creativity towards his creation. The writing of this article uses normative juridical research methods. The research specification uses descriptive analysis. This journal uses qualitative data analysis processing techniques. It is concluded from the results of the study that HKI protection efforts are needed for every form of work produced by UMKM entrepreneurs where the work has a high selling value. The role of the government as a policy maker, especially in controlling the economic sector, is to pay attention both in terms of socialization and assistance to UMKM in obtaining HKI certificates, with the aim that if a violation is committed by someone, they can take legal action, namely penalties.